Termination procedures of projects by the public works department (PWD) - Sanusi, Intan Safina (2015)
Termination of contract is one of the most significant problems in construction industry with major concern is given to public sector projects, as it has a direct relationship with the public and the nation’s socio-economic growth. Projects may suffer cost and time overrun and the owner may suffer significant loss and profit, worst still the project may be abandoned. From an observation report there were more than 50% of the projects in Ninth Malaysia Plan supervised by PWD are completed behind time. Some of these delays might be contributed by non-completed projects due to termination of contracts. The objective of this study is to identify the procedures of termination of contract by PWD. The research methodology adopted was the case study analysis based on the four (4) selected projects being implemented in the State of Johore, and terminated by PWD. The data and information were also gathered from interviews and documentary analysis. From the research findings there were five (5) salient procedures of termination of contract had been provided under Clause 51.1 of PWD 203A Standard Form of Contract and enumerated under Surat Arahan Ketua Pengarah Kerja Raya Bil.8/2013. PWD has complied with all the procedural requirements enumerated under the contractual provisions and guidelines, except with the timing for the issuance of Notice of Termination as well as to make the claim against the Contractor for the loss and/or damage caused to the Government to complete the project. This study is important to enhance the knowledge and understanding mainly for the public officials that termination of contract must be done with greatest care and must follow strictly all the procedural requirements, or otherwise such termination will be challenged by the Contractor before the court, and will be held as a wrongful termination.